The Multiplier Concept and Monetary Restraint: A Comment - Peake, Charles F. (Quarterly Journal of Economics, 1976)
Journal Article The Multiplier Concept and Monetary Restraint: A Comment Get access Charles F. Peake Charles F. Peake University of Maryland, Baltimore County (UMBC) Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 90, Issue 3, August 1976, Pages 515–517, https://doi.org/10.2307/1886050 Published: 01 August 1976